A highly selective decarboxylative deuteration of carboxylic acids. Issue 15 (11th March 2021) - Li, Nian; Ning, Yunyun; Wu, Xiaopeng; Xie, Jin; Li, Weipeng; Zhu, Chengjian
Abstract : A scalable, practical and general method for precise deuteration of aliphatic carboxylic acids via synergistic photoredox and HAT catalysis has been developed. The use of recirculation reactor achieved the preparative scale deuteration. Abstract : In this paper, we report a mild and practical method for precise deuteration of aliphatic carboxylic acids by synergistic photoredox and HAT catalysis. The reaction delivers excellent D-incorporation (up to 99%) at predicted sites even in substrates bearing reactive C–H bonds or versatile functional groups. The use of a recirculation reactor with a peristaltic pump supports a scalable preparative ability (up to 50 mmol) under very mild reaction conditions. The practical and precise deuteration of readily available complex carboxylic acids makes this protocol promising for the preparation of deuterium-labelled compounds.